Perception of residents regarding animal welfare in bullfighting events held in Huancavelica, Peru, 2023 - Cano-López, Renzo (2024)
The study aimed to describe the perception of Huancavelica residents regarding animal welfare in relation to bullfighting events. A survey consisting of 42 statements with Likert scale responses was applied to evaluate the following components: knowledge of animal welfare, animal mistreatment for pleasure, animal mistreatment due to ignorance, and the Animal Protection and Welfare Law. A total of 197 surveys were collected, corresponding to 125 men and 72 women. The majority of respondents demonstrated knowledge about animal welfare and expressed their disapproval of bullfighting. Specifically, 93.4% believed that animals should not be mistreated. 57.9% supported the prohibition of bullfighting in Huancavelica. 28.4% reported attending bullfighting events frequently, and 25.9% considered it an enjoyable activity. 69.0% affirmed that bullfighting violated the rights of fighting bulls, and 68.0% noted that the bull suffered during the event. 42.6% of Huancavelica residents did not consider bullfighting to be part of their culture, and 40.6% claimed to be aware of Law No. 30407, the Animal Protection and Welfare Law. They also expressed their opinions on the exclusion of fighting bulls from this law. The information obtained may serve to reopen the debate on the use of animals in cultural events and to assess its impact on animal welfare.